Analisis Pengukuran Produktivitas Overall Equipment Effevtiveness (OEE) pada Mesin Rotary di PT. XYZ - Rizal, Muhammad; Sulistyowati, Enik; Octavia, Ratna Dewi (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
PT. XYZ in the industrial world, increasing productivity and production efficiency is a key factor in achieving company goals, such as reducing defective products, and responding to increasingly stringent market demands. This study discusses the analysis of rotary strip machine productivity using the OEE (Overall Equipment Effectiveness) method which is used to measure the extent to which the rotary strip machine in the company works efficiently and effectively. Based on the results of data processing in this study, it can be concluded that the OEE calculation value obtained on the rotary strip machine at PT. XYZ with an average OEE value in October is 91% in November is 89%, and in December is 86%, in this value category according to JIMP the OEE value above 60% has met the standards set by the Japanese Institute of Plant Maintenance (JIPM) which is 85%. Soit can be considered to have a high effective value.